Cohesion policy or common agricultural policy - which of them is better suited to support rural development in Poland? - Wieliczko, Barbara (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Rural areas in Poland are underdeveloped in comparison to urban areas and lag much behind their counterparts in the EU-15. Thus, there is still a need to support their development to accelerate their socio-economic convergence with better-off parts of the EU. Rural development is part of CAP objectives, but it is also supported from cohesion policy, especially as part of regional development. The analysis presented tries to assess which of these policies is better suited to support rural development in Poland. The research is based on document analysis and meta-evaluation of earlier studies. The results show that rural development measures within the CAP and instrument under cohesion policy are generally complementary to one another. However, there is much room for closer cooperation between the two policies to enlarge their positive impact on rural development. It seems that CAP can be regarded as better suited for rural development as it is directly devoted to rural areas. Yet, it is still too agriculture-orientated and thus it offers insufficient amount of resources and not enough instruments for other sectors of rural economy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 466, s. 236-243
Keywords: cohesion policy; common agricultural policy; rural development; polityka spójności; wspólna polityka rolna; rozwój obszarów wiejskich